2015
DOI: 10.1016/j.trd.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

The longer and heavier vehicle debate: A review of empirical evidence from Germany

Abstract: HIGHLIGHTS• Evaluation of LHVs from a supply chain perspective.• An extensive range of trials in one country, Germany.• According to the findings, the vast majority of the research participants are interested in the adoption of LHVs regardless of the size of their companies.• The feasibility of LHVs is evaluated from eco-efficiency perspective. ABSTRACTThis paper aims to evaluate the likely effects of the adoption of Longer Heavier Vehicles (LHVs) from the perspective of logistics service providers (LSPs). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 18 publications
0
45
0
2
Order By: Relevance
“…13 Implementation of energy efficiency actions to improve road freight transport [91][92][93][94][95][96][97].…”
Section: Content Analysismentioning
confidence: 99%
“…13 Implementation of energy efficiency actions to improve road freight transport [91][92][93][94][95][96][97].…”
Section: Content Analysismentioning
confidence: 99%
“…Increasing the maximum permissible truck size and weight to more than 70 tons can decrease the carbon intensity [110], but could make road freight cheaper and induce a shift away from rail and water [3,12]. The effect on the relative share of road and rail freight of allowing LHVs varies by country, depending on the associated cost reductions and the fraction of rail freight that is containerized [110,180]. Predictions of the modal shift potential of LHV policies are difficult, since modal cross-elasticity values are uncertain and many current studies were conducted by groups with an interest in promoting one or the other mode [109,110].…”
Section: Truck Size and Weight Regulationsmentioning
confidence: 99%
“…A study in Sweden found that allowing longer vehicles capable of carrying two containers for intermodal drayage can reduce total intermodal transportation costs by 5%-10% [181]. There is a need for more research on role of LHVs for low-carbon intermodal freight transportation [180].…”
Section: Truck Size and Weight Regulationsmentioning
confidence: 99%
“…"A Review of Megatrucks" [3] highlighted the key findings from eight of these studies and stated that "there is widespread agreement that LHVs would reduce operating costs of road freight and greenhouse gas emissions per tonne-km of goods transported". Most research also agrees that vehicle mileage, transport costs, and emissions of road freight transport will be reduced on company level and also on national aggregate level if LHVs are introduced, or that these would increase if the LHVs currently in operation in countries such as Finland, Sweden, Canada, and Australia would be replaced with standard heavy goods vehicles [3,[10][11][12][13].…”
Section: Possible Impacts Of Lhvs Based On Literaturementioning
confidence: 99%